IMPROVING ENGLISH STUDENTS’ SPEAKING SKILLS THROUGH AN ACTION LEARNING STRATEGY - Kasmaini Kasmaini; Sudarwan Danim; Muhammad Kristiawan; Zahrida Zahrida; Sufiyandi Sufiyandi; Dwi Maharrani (University of Kuningan, 2023)
For students of English education, speaking skills are of paramount importance. However, in the context of English students at Universitas Bengkulu, many students seemed to still struggle with speaking skills. Therefore, to cope with this problem, this classroom action research was conducted with the aim of improving the speaking skills of students who took English conversation course by applying action learning strategy (ALS) since this strategy was scientifically promising. Two phases of the class action design were employed in this research project. The data were garnered using observations, interviews, and English-speaking test. It was evident from the first phase of observation that almost all students recommended the ALS. The data from the interview revealed that a significant proportion of students had profited from this approach, and there were few students who spoke in front of the class. The first phase's precise decision how an average score of 74 was attained by the students. At the second phase, the observation and interview data showed that nearly all students actively participated during discussions and had good improvements of English-speaking skills. The result revealed that the implementation of ALS in the conversation course in semester 1 improves S1 students’ speaking skills.